1989- “Beef is safe.” 1996- “Not.” (The Scientific World Journal)
A sharply critical government report on the administration of mad-cow disease research leads the news from Nature this week. Science also covers the story, but they lead with librarians protests over a proposed merger of two science publishing giants.